Air disaster Canberra : the plane crash that destroyed a government - Tink, A. A. (Andrew A.) (NewSouth Pub., 2013)
1940. Wartime Australia. Key members of Menzies' government die in a fiery plane crash. What went wrong and what happened next? In August 1940 Australia had been at war for almost a year when a plane a Hudson A16 97 carrying ten people, including three cabinet leaders, crashed into a ridge near Canberra.